Truncated matrix trigonometric problem of moments: operator approach - Zagorodnyuk, S. M. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study the truncated matrix trigonometric moment problem. We obtain parametrization of all solutions of this moment problem (in both nondegenerate and degenerate cases) via an operator approach. This parametri-zation establishes a one-to-one correspondence between a certain class of analytic functions and all solutions of the problem. We use important results on generalized resolvents of isometric operators, obtained by M. E. Chumakin.